Wartość prognostyczna wyników testu z fizyki stosowanego na egzaminie wstępnym w odniesieniu do wyników z biofizyki studentów I roku Wydziału Lekarskiego AM w Poznaniu - Kucharski, Marian (Wydawnictwo Naukowe UAM w Poznaniu, 1996)
Research into the diagnostic accuracy of the results in physics established in entrance examinations in the Department of Physician Training (Medical School) of the Academy of Medicine in Poznań in the years 1989,1990,1992 and 1993. The criteria used to establish the level of accuracy were the results achieved by first year student's in biophysics. Reasonable diagnostic accuracy emerged, but only with reference to a standardized criterion in a trial examination in biophysics.
Keywords: nabór studentów; program dydaktyczny; egzamin testowy; biofizyka; studia medyczne; medycyna; entrance examination; biophysics; medical school; test; Neodidagmata